2007
DOI: 10.1890/06-1664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Decades of Fire Manipulation on Woody Vegetation Structure in Savanna

Abstract: The amount of carbon stored in savannas represents a significant uncertainty in global carbon budgets, primarily because fire causes actual biomass to differ from potential biomass. We analyzed the structural response of woody plants to long-term experimental burning in savannas. The experiment uses a randomized block design to examine fire exclusion and the season and frequency of burn in 192 7-ha experimental plots located in four different savanna ecosystems. Although previous studies would lead us to expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
442
3
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(495 citation statements)
references
References 29 publications
(39 reference statements)
30
442
3
11
Order By: Relevance
“…Data from another long-term, plot-based and well-reported fire experiment in the Kruger National Park (South Africa) with similar mean annual precipitation to the present study site, also showed fire frequency had no significant effect on tree density (Higgins et al 2007) as well as woody species richness and composition (Van Wilgen et al 2007). These previous studies did not evaluate the effect of frequency of burning on alien plant invasions in African savannas and as far as we are aware, no alien species were found at the Kruger experiment (Higgins et al 2007;Van Wilgen et al 2007). It may well be that for the Zimbabwean experimental site, many alien species established because the experiment was located at an agricultural research site with a long history of anthropogenic disturbance, specifically pasture improvement.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Data from another long-term, plot-based and well-reported fire experiment in the Kruger National Park (South Africa) with similar mean annual precipitation to the present study site, also showed fire frequency had no significant effect on tree density (Higgins et al 2007) as well as woody species richness and composition (Van Wilgen et al 2007). These previous studies did not evaluate the effect of frequency of burning on alien plant invasions in African savannas and as far as we are aware, no alien species were found at the Kruger experiment (Higgins et al 2007;Van Wilgen et al 2007). It may well be that for the Zimbabwean experimental site, many alien species established because the experiment was located at an agricultural research site with a long history of anthropogenic disturbance, specifically pasture improvement.…”
Section: Discussionsupporting
confidence: 68%
“…Previous research published on this long-term fire experiment revealed that regular burning reduced tree size regardless of the frequency of burning, but failed to eliminate woody plants, or significantly alter tree species diversity at the experimental site (Furley et al 2008). Data from another long-term, plot-based and well-reported fire experiment in the Kruger National Park (South Africa) with similar mean annual precipitation to the present study site, also showed fire frequency had no significant effect on tree density (Higgins et al 2007) as well as woody species richness and composition (Van Wilgen et al 2007). These previous studies did not evaluate the effect of frequency of burning on alien plant invasions in African savannas and as far as we are aware, no alien species were found at the Kruger experiment (Higgins et al 2007;Van Wilgen et al 2007).…”
Section: Discussionsupporting
confidence: 39%
“…High-intensity fires are typical of the late dry season particularly just before the rainy season starts. Long-term fire experiments have shown that early-season burns allow a much broader range of fire-resistant and fire-sensitive trees to occupy a savanna [9,[65][66][67]. By contrast, late-season burns are much more damaging to trees, and only the most fireresistant species survive frequent late-season burns.…”
Section: Grass-fuelled Fire Regimesmentioning
confidence: 99%
“…It may be possible to obtain more intense fires by increasing the fire interval (Higgins et al, 2007); however variations of fire return over 1, 2, and 3 years elsewhere have shown to impact woody stem density both positively and negatively (Higgins et al, 2007) and evidence from elsewhere in Gabon suggests that woody stems may even increase with increased fire frequency (Walters, 2012). In a high rainfall savannah such as Lopé, it is possible that an early, short dry season burn will reduce fuel loads and therefore the intensity and efficacy of the ensuing late season burn (Higgins et al, 2000).…”
Section: Parks Vol 201 March 2014mentioning
confidence: 99%